Ahammiyat Ta‘allum al-Arabiyyah wa Tarâiq Ta‘lîmiha ‘inda Ibn Taimiyah - Gumilar, Rizki (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
Abstract: Purpose-It is stated that Ibn Taimiyah was a scholar who spoke fluent Arabic, was fast in reading, and straightforward, not only fluent in speaking, but also proficient in Arabic grammar. Likewise, it is said that he had read the Book of Sibawaih in front of his teacher, Shaykh Ibn Abdul Qawi in 6 days, until he understood it and mastered the science of nahwu. On the basis of this story and his success in learning Arabic, the researcher was moved to collect his sayings about the importance of learning Arabic and how to teach it, especially for non-Arabic speakers. Design/Methodology/Approach-This research is guided by the descriptive analysis method, by collecting the required data from the books of Ibn Taimiyah, both from printed references, e-books, and software of Maktabah Syamilah. After the data was collected, the Researcher brought a number of words from classical and contemporary scholars who supported Ibn Taimiyyah's words. Findings: From this research, the Researcher got fifteen sayings of Ibn Taimiyyah about the importance of learning Arabic and ten methods of teaching it. All of his sayings about the importance of learning Arabic are related to religious issues, so it can be concluded that the purpose of learning Arabic according to him is to understand religious texts. Research Limitation/Implications:This research is certainly not relevant for those who want to study Arabic for general purposes, because Ibn Taymiyyah limited it to religious purposes only. Nevertheless, this research enriches Arabic teaching methods for specific purposes for non-Arabic speakers.